The art and archaeology of bodily adornment
1 online resource
Keywords: "This book examines the significance of adornment to the shaping of identity in mortuary contexts within Asia, and brings these perspectives into dialogue with current scholarship in other worldwide regions. The mortuary contexts of focus in this volume represent unique sites and events where identity was visualized, and often manipulated and negotiated, through material objects and their placement on and about the deceased body. In both breadth and depth, it will be of interest to students and scholars interested in the archaeology, art, and history of Central and East Asia, as well as anyone interested in the general study of dress and adornment"--